Michel Foucault e a governamentalidade (Bio) política: o domínio da técnica no processo de fabricação da vida - BRITO, Keline da Costa (2023)
The research aims to analyze how the processes of production of life have been constituted in the face of new strategies of power, developed under the sign of technosciences. This shows a scenario of evolution, since it is possible to understand that life is not only linked to the natural order, but can also be artificialized. In order to establish the limits of this extensive theme, we will analyze how the philosophy of Michel Foucault, in his late writings, contributes, above all, to a reflection about the current challenges regarding biopolitical mechanisms and the progress of medical technologies in the domination and augmentation of life. To this end, we start from the premise that with the advent of neoliberal governmentality a process of constitution of entrepreneurial societies has worked. This event has not only redefined the social structure, but also the potentiality of politics, its role in life, and the way of using technical apparatuses, directly affecting man with regard to greater longevity, health, memory, and strength. Such transformations intertwine life in the logic of power, making it the basis of virtually unlimited new knowledge and economic management. In view of this, the technique of biological modeling has become a possibility to put an end to the biological dangers that threaten man, as it possesses the ability to intervene and recombine the randomness of existence. Moreover, our vitality calls for care that is not only established by the organs of the state, but that the individual himself develops and applies to himself. In this sense, biopolitics conquers new spaces and methods in the sense of requalifying the social and cultural conjuncture in the promotion of a better quality of life, reinventing itself in the administration of the States without leaving aside its central concerns. In this way, it is increasingly evident that the new technologies of power produce changes in the meanings and tendencies of life, since it is perceived as a biological form that can be perfected, manipulated, and, thus, the individual becomes a product of politics.